Legal Deconstruction of Digital Consumer Protection through the Potential Implementation of Data Portability Principles in Indonesia - Raden Budi Nurjaman; Yuyut Prayuti (PDIH Untag Semarang, 2025)
This research analyzes the effectiveness of legal protection for consumers in digital business transactions in Indonesia through the principle of data portability, focusing on the financial technology and electronic commerce sectors. Indonesia ranks thirteenth globally in data breaches, with around 156.8 million personal data records leaked from 2004 to April 2024. Since 2017, the Financial Services Authority has closed more than eleven thousand illegal financial entities, many of which misused consumer data. These problems show the urgent need for stronger rules to give consumers better control over their personal information. The study aims to examine how the principle of data portability is applied in practice and how the Consumer Protection Law and the Personal Data Protection Law can work together to create a safer digital environment. It uses a normative juridical method with statutory, comparative, and case study approaches. The findings reveal that most businesses lack proper systems for data transfer and have not reached international standards. The main obstacles are the absence of clear technical guidelines, limited supervision resources, and low awareness among companies. In conclusion, stronger government regulations, better infrastructure, multi-stakeholder support, and public education are needed to make data portability a real tool for protecting digital consumers and building trust in Indonesia’s growing digital economy.